Centralization of Pancreatic Surgery Improves Results: Review. (March 2020) - Ahola, R.; Sand, J.; Laukkarinen, J.
Background and Aims: The effect of operation volume on the outcomes of pancreatic surgery has been a subject of research since the 1990s. In several countries around the world, this has led to the centralization of pancreatic surgery. However, controversy persists as to the benefits of centralization and what the optimal operation volume for pancreatic surgery actually is. This review summarizes the data on the effect of centralization on mortality, complications, hospital facilities used, and costs regarding pancreatic surgery. Materials and Methods: A systematic librarian-assisted search was performed in PubMed covering the years from August 1999 to August 2019. All studies comparing results of open pancreatic resections from high- and low-volume centers were included. In total 44, published articles were analyzed. Results: Studies used a variety of different criteria for high-volume and low-volume centers, which hampers the evaluating of the effect of operation volume. However, mortality in high-volume centers is consistently reported to be lower than in low-volume centers. In addition, failure to rescue critically ill patients is more common in low-volume centers. Cost-effectiveness has also been evaluated in the literature. Length of hospital stay in particular has been reported to be shorter in high-volume centers than in low-volume centers. Conclusion: The effect of centralization on the outcomes of pancreatic surgery has been under active research and the beneficial effect of it is associated especially with better short-term prognosis after surgery.